Debt Management Performance Assessment : Zambia - World Bank (World Bank, Washington, DC, 2019)
The objective of the mission was to assess the debt management strengths and areas in need of reform through the application of the Debt Management Performance Assessment (DeMPA) methodology. DeMPA mission delivered technical assistance in evaluating the legal, institutional and regulatory framework in government debt management.The revised 2015 DeMPA methodology provides a comprehensive set of indicators spanning the full range of debt management (DeM) functions. The results of the DeMPA evaluation help the authorities to take stock of the current debt management situation and design medium term priority reforms. Overall, some improvements on DeMPA scores compared to the latest assessment in 2011 could be observed. Areas of strength include the publication and implementation of the debt management strategy 2017-19, staff capacity, and debt sustainability analysis (DSA). Further improvements include the completion of external financial audits, the elaboration of an annual borrowing calendar covering all government securities, the involvement of legal advisers throughout the negotiation of external borrowing and the elaboration of draft procedures manual.The publication of the debt management strategy 2017-19 is an important step towards strengthening debt management and is a main achievement that is fully recognized by the DeMPA assessment team. Since the strategy has only been published recently and it, therefore, is not possible to verify that the strategy is updated annually, this achievement is not reflected in the scores in this DeMPA.Challenges include the fragmented databases, delays in update of debt records, and lack of formalized procedures. Procedure manuals are in draft form and has not yet been validated and could not be fully reflected in the assessment. Procedures for accessing the international market, mobilizing domestic funding other than through security issuances, and issuing guarantees have not been elaborated.